Differences in Functional Outcome Across Subtypes with Spetzler‐Martin Grade II Arteriovenous Malformations. Issue 3 (September 2017) - Hung, Alice L.; Yang, Wuyang; Westbroek, Erick M.; Garzon‐Muvdi, Tomas; Caplan, Justin M.; Braileanu, Maria; Wang, Joanna Y.; Colby, Geoffrey P.; Coon, Alexander L.; Tamargo, Rafael J.; Huang, Judy
Abstract : BACKGROUND: : The Spetzler‐Martin grading system for brain arteriovenous malformations (AVMs) is based on size (S), eloquence (E), and deep venous drainage (V). However, variation exists due to subgroup heterogeneity. While previous studies have demonstrated variations in outcomes within grade III AVMs, no studies have focused on grade II AVM subtypes. OBJECTIVE: : We aim to delineate how functional outcomes differ among patients with subtypes of grade II AVMs. METHODS: : We retrospectively reviewed patients with AVMs evaluated at our institution from 1990 to 2013. Grade II AVMs were divided into 3 subtypes: group 1 (S2V0E0), group 2 (S1V0E1), and group 3 (S1V1E0). Baseline characteristics were compared, and functional status was assessed using the modified Rankin Scale (mRS) at pretreatment and last follow‐up. Differences in mRS between the 2 time points were compared. RESULTS: : A total of 208 grade II patients (34.0%) were retrieved from 611 graded patients. After accounting for missing data, our cohort consisted of 137 patients. Mean age of all patients was 37.2 years, with 74 females (54.0%). No significant difference was observed across subgroups for pretreatment mRS ( P = .096), treatment modalities ( P = .943), follow‐up durations ( P = .125), and mRS at last follow‐up ( P = .716). In a subgroup analysis between group 1 and group 3, more patients with worsened mRS were observed in group 3 ( P = .039). This distinction was further confirmed in surgically treated patients ( P = .049), but not in patients treated with radiosurgery ( P = .863). CONCLUSION: : Subtypes of grade II AVMs portend different posttreatment gains in functional outcome. Group 1 (S2V0E0) patients had the best functional outcome gain from treatment, while group 3 (S1V1E0) patients fared less well, particularly with surgical treatment.